WSe2 nanoribbons: new high-performance thermoelectric materials. Issue 24 (2nd June 2016) - Chen, Kai-Xuan; Luo, Zhi-Yong; Mo, Dong-Chuan; Lyu, Shu-Shen
Abstract : Armchair WSe2 nanoribbon structures are predicted to exhibit outstanding thermoelectric performance, mainly attributed to the ribbon edge disorder. Abstract : In this work, for the first time, we systematically investigate the ballistic transport properties of WSe2 nanoribbons using first-principles methods. Armchair nanoribbons with narrow ribbon width are mostly semiconductive but the zigzag nanoribbons are metallic. Surprisingly, an enhancement in thermoelectric performance is discovered moving from monolayers to nanoribbons, especially armchair ones. The maximum room-temperature thermoelectric figure of merit of 2.2 for an armchair nanoribbon is discovered. This may be contributed to by the effects of the disordered edges, owing to the existence of dangling bonds at the ribbon edge. H-passivation has turned out to be an effective way to stabilize the edge atoms, which enhances the thermodynamic stability of the nanoribbons. In addition, after H-passivation, all of the armchair nanoribbons exhibit semiconductive properties with similar band gaps (∼1.3 eV). Our work provides instructional theoretical evidence for the application of armchair WSe2 nanoribbons as promising thermoelectric materials. The enhancement mechanism of the disordered edge effect can also encourage further exploration to achieve outstanding thermoelectric materials.